PRESENTATION OF ELEGY AND ROMANTISM IN A COLLECTION OF POETRY SAPARDI DJOKO DAMONO - Gazali Lembah; Pratama Bayu Santosa; Ade Nurul Izatti; Munianti Munianti (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
The problem in this research is how to present elegy and romanticism in Sapardi Djoko Damono's poetry collection. The purpose of this study was to identify and describe elegy and romanticism in Sapardi Djoko Damono's poetry. The method used in this study is a qualitative descriptive method. The source of the data in this study is a collection of Sapardi Djoko Damono's poems. In this study, the authors used data collection techniques, namely reading and taking notes. The elegy presentation is a lamenting poem that expresses one's sorrow and romantic presentation is part of the poem that contains the overflow of one's love for the lover. The elegy presentation consists of a presentation to the creator and partner. The presentation of the elegy to the creator referred to in this study is a servant who always remembers death, a servant who always remembers sins while living on earth. The presentation of elegy to the couple in question in this study is a pair of lovers, one of whom has ordinary feelings towards their partner and elegy to this couple also because of the distance and circumstances that separate the lovers in this study, so that the two cannot meet. While the presentation of romance is also divided into two, namely the presentation of romance to the creator and partner. The creator referred to in this study is a servant who prays for peace and peace with love and a servant who is always grateful for the love given by his Lord through various blessings in life. While the presentation of romanticism to the couple referred to in this study is a sincere love for their partner who is willing to do anything for the sake of their loved ones and always gives attention and affection to each other.